The Effect of Inflation, Exchange Rates, and Interest Rates on The Jakarta Composite Index in The Indonesia Stock Exchange During The Period Of 2017-2022 - Mutiara Indah Purnamasari; Enji Azizi; Djaka Adiwinata (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the effect of inflation, exchange rates, and interest rates on the Jakarta Composite Index (JCI) in the Indonesia Stock Exchange (IDX) during the period of 2017-2022, both partially and simultaneously. The approach used is quantitative with time series data covering inflation, exchange rates, interest rates, and the JCI. The data used in this study consists of 288 observations, with each variable having 72 data points. The analysis method includes multiple linear regression, classical assumption testing, hypothesis testing, and coefficient of determination, with the help of SPSS 27.0 software. The results of the study show that: (1) inflation has been positive and significant effect on the JCI, (2) exchange rates have a positive but insignificant effect on the JCI, (3) interest rates have a negative and significant effect on the JCI, and (4) simultaneously, inflation, exchange rates, and interest rates have a significant effect on the JCI in the Indonesia Stock Exchange during the period of 2017-2022.